Vom Antijudaismus zum Hass auf Israel - Grigat, Stephan (Verlag Barbara Budrich, 2025)
How can hatred of Israel be explained? Where does the deep-rooted anti-Semitism that exists in both the Western and the Arab world come from? Stephan Grigat sheds light on the different faces of anti-Semitism - from Christian and Islamic anti-Judaism to modern anti-Semitism and anti-Zionism. It examines how these forms of hatred not only emerge from historical roots, but also operate as ideologies in political movements on both sides of the political spectrum - from Arab nationalism to political Islam.